Pro-oxidants in pathogenesis of severe malaria in children - Narsaria, Nidhi; Singh, Ashutosh Kumar; Mishra, Pankaj Kumar; Luthra, Megha (Indian Journal of Community Health, 2015)
Introduction: Malaria is a major cause of morbidity and mortality in developing countries. The role of oxidants in the pathogenesis of malaria in children are lacking. Objective: This study was done to assess the plasma oxidant level of children with severe malaria. Material and Methods: This prospective study was done in Mayo Institute of Medical Sciences, a tertiary care hospital. 40 patients of confirmed malaria in the age group of 0–16 years and other 40 age- and gender-matched healthy children (controls) were included in our study. Plasma malonyldialdehyde (MDA) was estimated by thiobarbituric acid test. Protein carbonyl level was analyzed by the methods of Reznick and Packer. Results: The average plasma level of oxidants was significantly higher in cases as compared to control group (p < 0.05). The plasma MDA level in the cases was significantly higher (p= 0.03) than in control group. The plasma level of protein carbonyl in cases was significantly higher (p = 0.038) as compared to control group. The plasma level of Copper (Cu) and Nitrite were also found significantly higher (p < 0.05) in cases. Conclusion: The plasma MDA, protein carbonyl, copper and nitrites were significantly raised in cases with severe malaria as compared to controls (p <0.05) reflecting the increased oxidative stress in cases as compared to controls.